A Case of Hyperekplexia That Started From Childhood: Clinical Diagnosis With Negative Genetic Investigations - Antonioni, Annibale; Peschi, Giovanni; Granieri, Enrico (Frontiers in Neurology, 2020)
Here, we report the case of a 63-year-old woman affected by abnormal, excessive and involuntary reactions to harmless and unexpected sensory stimuli, compatible with the diagnosis of hyperekplexia. It is a pathology that involves the glycinergic system on a hereditary basis and, even if genetic proof compatible with the diagnosis is not present in this case, the fact that an aunt on her father’s side manifested the same disorders supports the clinical suspicion. From an early age, clinical history shows anomalous motor manifestations, initially framed as a form of focal epilepsy or ordinary disorders of the mood sphere, later excluded by the lack of effectiveness of a targeted therapy. Despite this, intellectual, psychological and socio-emotional development was regular. The manifestations, present throughout childhood, adolescence and early adulthood in moderate entity, worsened after the age of 50 perhaps due to hormonal changes. The presence of consequent anxiety and depression has compromised her quality of life, and in order to improve it therapies were resorted which, however, involve cognitive-attention deficits. No diagnostic test has confirmed the diagnosis, although some scars in brain areas involved in the control of reactions are elements favorable to the condition in genetically predisposed subjects. Therapies currently in use attenuate the motor symptomatology without resolving it and cause side effects in the psychological and cognitive sphere. In this case, we want to highlight the difficulty of diagnosing a very rare genetic condition, still not well known and presenting symptoms which are easily confused with other more common diseases, in the absence of clinical-diagnostic tools at the present time.